2017
DOI: 10.1016/j.neuron.2017.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Structural Bases of Desensitization in AMPA Receptor-Auxiliary Subunit Complexes

Abstract: SUMMARY Fast excitatory neurotransmission is mediated by AMPA-subtype ionotropic glutamate receptors (AMPARs). AMPARs, localized at post-synaptic densities, are regulated by transmembrane auxiliary subunits that modulate AMPAR assembly, trafficking, gating and pharmacology. Aberrancies in AMPAR-mediated signaling are associated with numerous neurological disorders. Here, we report cryo-EM structures of an AMPAR in complex with the auxiliary subunit GSG1L in the closed and desensitized states. GSG1L favors the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
161
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(178 citation statements)
references
References 82 publications
(131 reference statements)
9
161
1
2
Order By: Relevance
“…Deletion of L1 from g2 and g8 approximately halved the steady state current (15 ± 2 and 15 ± 3%, n = 11 and 15, for g2 DL1 and g8 DL1, respectively; Figure 2B and D and Table 1), with a barely detectable speeding up of entry to desensitization (60 ± 5 s -1 , n = 11 and 15, for g2 DL1 and g8 DL1, respectively; Figure 2B and C and Table 1). These results suggested that L1 can influence desensitization of complexes, as shown recently for GSG1L (Twomey et al, 2017a) but the absence of a simple exchange in desensitization behavior suggested that this loop functions in concert with other modulatory elements. …”
Section: Modulation Of Fast Ampa Receptor Gating By Tarp L1 and L2 Sesupporting
confidence: 77%
See 3 more Smart Citations
“…Deletion of L1 from g2 and g8 approximately halved the steady state current (15 ± 2 and 15 ± 3%, n = 11 and 15, for g2 DL1 and g8 DL1, respectively; Figure 2B and D and Table 1), with a barely detectable speeding up of entry to desensitization (60 ± 5 s -1 , n = 11 and 15, for g2 DL1 and g8 DL1, respectively; Figure 2B and C and Table 1). These results suggested that L1 can influence desensitization of complexes, as shown recently for GSG1L (Twomey et al, 2017a) but the absence of a simple exchange in desensitization behavior suggested that this loop functions in concert with other modulatory elements. …”
Section: Modulation Of Fast Ampa Receptor Gating By Tarp L1 and L2 Sesupporting
confidence: 77%
“…Because in these experiments, slow desensitization occurs when occupancy of superactive states is low, we can quite reasonably assume that L1 adopts multiple conformations to stabilize separate functional states of the receptor, and that some functional signatures require a concerted action of both loops. Additional stabilization of desensitized states by the variable loop 1 is also likely (Twomey et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used cryo-EM to analyze the structure of the homomeric GluA2 flip splice variant AMPAR in complex with the auxiliary subunit germline-specific gene 1-like (GSG1L), which we surmised would stabilize the closed-state structure of the ion channel as it lowers the ion channel open probability compared to the transmembrane AMPAR regulatory protein (TARP)-γ2 or stargazin (STZ) 15,16 . Indeed, using a covalent fusion construct (Methods) between truncated forms of GluA2 and GSG1L, we solved structures of the digitonin-solubilized receptor complex bound to the antagonist ZK200775 (ZK) in two states, termed GluA2-GSG1L ZK-1 (4.6 Å) and GluA2-GSG1L ZK-2 (4.4 Å) (Extended Data Table 1; Extended Data Fig.…”
Section: Ion Channel Structurementioning
confidence: 99%